DEVELOPING DESCRIPTIVE WRITING MATERIAL THROUGH TEXT-LESS COMIC FOR GRADE X OF SMA GEMA BUWANA - Fitri Atika; Yeni Erlita (Universitas Negeri Medan, 2021)
The aim of this study was to develop descriptive writing material through text-less comic for grade X of SMA GEMA BUWANA. The research was conducted by using Research and Development (R & D) design through six stages; gathering data and information, analyzing data, designing text-less comic, validating by the experts, revising and final product. The subject of the study was grade ten of SMA GEMA BUWANA. The data were gathered by administering interview to English teacher and distributing questionnaire to 25 respondents to get the students’ needs. The interview and questionnaire result prove that the students need text-less comic in teaching writing which can stimulate students’ ability and develop thinking process through looking for, guessing, and logically. Using text-less comic in learning process also helps students to understand the material by themselves. The product has been validated by an English lecturer and an English teacher with the interval was 4.3. The product was categorized as “Very Good” descriptive writing material through text-less comic. The final product of this study was a material of developed descriptive writing material through text-less comic, it consisted one part that has 3 kinds of descriptive cover the learning needs.Keywords: Text-Less Comic, Descriptive Writing Material, Research and Development (R & D)